CREDIT RISKS AND FACTORS LEADING TO A DECREASE IN ASSET QUALITY: ANALYSIS BASED ON FOREIGN EXPERIENCE (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This article provides a comparative analysis of macroeconomic factors, institutional conditions, and prudential mechanisms that influence the dynamics of credit risks and non-performing loans (NPL). The study reveals the institutional interpretation of the differences between "lag effect," IFRS 9 and expected credit loss (ECL) reserves and NPL. The obtained results indicate the need to strengthen the structure of the loan portfolio and proactive risk monitoring in the banking system of Uzbekistan.
Keywords: Credit risk, asset quality, NPL, IFRS 9, ECL, macroeconomic factors, macroprudential policy, restructuring, latent risk, bank stability.